Public Opinion about Drinking Water Issues in Florida - Tatiana Borisova; John Brett; Cassel Gardner (EDIS, 2010)
FE843, a 10-page illustrated report by Tatiana Borisova, John Brett, and Cassel Gardner, summarizes the results of a public survey about the drinking water issues in Florida. Published by the UF Department of Food and Resource Economics, October 2010.